Low Grade Endometrial Stromal Sarcoma with Widespread Metastasis: A Rare Case Report - Sethi, Neha; Pande, C L; Sharma, Anjali; Pandia, Kirti (Annals of Pathology and Laboratory Medicine, 2019)
EST are rare tumors. According to WHO classification, they are divided into Endometrial stromal nodules (ESN), Low grade endometrial stromal sarcomas (LGESS) and Undifferentiated stromal sarcomas (USS) according to mitotic activity, vascular invasion and difference in prognosis. EST may be misdiagnosed as benign tumors especially in small biopsies. This may lead to increased risk of spread in patients at the time of final diagnosis. We report an interesting case of a premenopausal woman who presented with LGESS in a very widespread manner. In the present study, characteristic histopathology and IHC was really an adjunct to diagnose the case and a panel of antibodies put together like Caldesmon, SMA, PR, ER, Desmin and B-Catenin helped a lot to diagnose it.